S. R. Ranganathan : An Exemplary Teacher and a Guide - Singh, Harjit (DESIDOC Journal of Library & Information Technology, 2002)
Dr Ranganathan had moved over to Bangalore in 1957. He was responsible for the establishment of DRTC at Bangalore in 1962 under the Indian Statistical Institute (ISI). Calcutta. The main objective of the Centre was to conduct research and teaching in library sciences.Dr Ranganathan served as an honorary professor of DRTC during 1962-72. Although I had heard earlier about this famous librarian, I got the first opportunity to come in contact with him when I joined DRTC. http://dx.doi.org/10.14429/dbit.12.5.3063